BCI Tech in Gaming Training and Education - Shafeeg, Abdulla; Shazhaev, Ilman; Tularov, Arbi; Shazhaev, Islam; Mihaylov, Dimitry (AI Society & STMIK Indonesia, 2023)
BCI as a technology has been developing relatively quickly in the past several decades. Numerous gadgets and devices have been presented on the market. Yet, if most of them are related to medicine and partly education, there are not as many which have to do with ultimate gaming. Of course, wearable devices constitute the sphere of medical data acquisition. However, none of them have to do with gaming education and training. This paper presents an overview of the existing BCI models focused on gaming. It suggests an experimental system justifying its necessity in the impact it would have on the gaming world. The utilization of BCI capabilities in developing a relatively new direction can change the sphere of gaming training altogether.